Two case studies in veterinary forensic imaging and a brief literature review. (June 2020) - Watson, Elizabeth; Baucom, Kristina J.
Highlights: Interest in prosecution of animal crime has increased. Animal abuse and child abuse, elder abuse and domestic violence are linked. Imaging studies provide input in prosecution of crimes against animals. Documentation of imaging findings in animal abuse cases are needed to advance the field of veterinary forensic imaging. Abstract: Over the past 35 years societal changes and knowledge that animal crimes may occur in conjunction with child abuse, elder abuse and domestic violence has increased awareness and interest in prosecuting crimes against animals and suggests that those outside the veterinary community would have an interest in the current state of veterinary forensic medicine. Imaging studies are often performed to supplement live animal and post mortem forensic examinations. With increased access to cross sectional imaging modalities, computed tomography (CT) will be performed in addition to radiography in many medicolegal cases involving neglect and abuse in animals. This manuscript presents two veterinary forensic imaging case studies and provides a brief literature review of the North American perspective of veterinary forensic science.